81.4k views
2 votes
F(x) = x^2 - 5x - 14

g(x) = x - 7

(f + g)(-3) =
(f - g)(-3) =
(g - f)(-2) =

User Kjetilh
by
4.6k points

1 Answer

4 votes

Answer:

See attached image.

Explanation:

Calculate the vales of each function (f and g) for the value of x as indicated. Then perform the arithmetic operation on the results. For example:

f(-3) = 10

g(-3) = -10

Then (f+g)(-3) is 10 - 10 = 0

(f-g)(-3) is 10 -(-10) = 20

and so on, as shown.

F(x) = x^2 - 5x - 14 g(x) = x - 7 (f + g)(-3) = (f - g)(-3) = (g - f)(-2) =-example-1
User Cfi
by
4.6k points